2012
DOI: 10.1155/2012/391917
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Radiotherapy versus Postoperative Radiotherapy of Patients with Oro- and Hypopharyngeal Cancer: Impact of Prognostic Factors

Abstract: Purpose. To compare the impact of prognostic factors of patients treated with definitive radio(chemo)therapy versus patients treated with surgery and postoperative radiotherapy for squamous cell carcinoma of the oro- and hypopharynx.Patients and Methods. 162 patients treated with definitive radiotherapy and 126 patients treated with postoperative radiotherapy were retrospectively analysed. The impact of the prognostic factors gender, age, total tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Total tumor volume is a well known prognostic parameter that impacts on the loco-regional management and OS. Such a factor should be taken into account for the selection of high-risk patients and for their stratification in clinical trials or statistical analyses, as suggested by Rudat et al ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Total tumor volume is a well known prognostic parameter that impacts on the loco-regional management and OS. Such a factor should be taken into account for the selection of high-risk patients and for their stratification in clinical trials or statistical analyses, as suggested by Rudat et al ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, young patients (≤40 years) accounted for 24.4% of the total BC cases, which is comparable to other Asian countries, such as China, 18 South Korea, 19 Iran, 20 Pakistan, 21 and the United Arab Emirates (UAE). 22 However, it is significantly higher than the 3.7%-6.6% reported in many Western countries. [4][5][6][7] The higher rate of BC in young patients in our cohort is comparable with the previous data from Saudi women reported by Nuzhat et al 23 and older patients (p=0.174).…”
mentioning
confidence: 77%
“…Treatment related toxicity; the need for permanent gastrostomy tube placement and overall preservation of laryngo-esophageal function remains low. 16 In the advanced stage setting, CRT is frequently proposed for patients in whom functional status has not been irreversibly compromised. Otherwise, a primary surgical approach followed by postoperative RT is typically adopted.…”
Section: Patients Who Achieved Favorable Outcomes Were Pooled To Evaluate Efficacy and Risk Ratio Viamentioning
confidence: 99%